Pollen analysis from Early and Middle Holocene archaeological sites in the Blue Nile area, Central Sudan Análisis palinológicos en yacimientos arqueológicos del Holoceno Inicial y Medio en el área del Nilo Azul, Sudán Central - López Sáez, José Antonio; López García, Pilar (Complutum, 2003)
Palynological analysis has been carried out on six samples collected from two Early Holocene sites (Sheikh Mustafa and El Mahalab) and one Middle Holocene site (Sheikh el Amin) in the Blue Nile area, Central Sudan. The taphonomic problems derived from the sedimentary contexts studied here are discussed. The results of the analysis indicate that natural (and to some extent anthropic) factors shaped a savanna-grassland type of environment during Early-Middle Holocene in the area being studied.